POTENSI SENYAWA BIOAKTIF DARI EUCHEUMA COTTONII TERHADAP GEN NS5 DAN ENVELOPE (E) VIRUS DENGUE SERTA TARGET ACHE DAN OBP PADA AEDES AEGYPTI: TINJAUAN MINI - Vincentia Ade Rizky; Maria Selviana Joni; Umi Latifah; Ni’mah Hidayatul Laili; Eka Nurul H.P.S; Avinda Sari Kanthi Rahayu; Rachmat Saleh; Nasrullah Tamrin; Awaluddin; Adipura Atmadja Egok; Tri Astuti Sugiyatmi (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Dengue fever remains a major global health concern, especially in tropical regions, due to increasing insecticide resistance and the absence of specific antiviral treatments. Marine-derived natural products, such as those from Eucheuma cottonii, offer promising alternatives. This mini-review aims to evaluate the potential of E. cottonii bioactive compounds targeting molecular markers of Aedes aegypti mosquitoes and the Dengue virus (DENV). A review of 30 relevant national and international articles published between 2015 and 2025 was conducted, focusing on the larvicidal and antiviral activities of E. cottonii. E. cottonii contains flavonoids, alkaloids, terpenoids, and sulfated polysaccharides. These compounds inhibit AChE and OBP enzymes in mosquito larvae and target the NS5 and Envelope (E) proteins of DENV. The antiviral effects are also enhanced by its antioxidant and immunomodulatory activities. Eucheuma cottonii has a significant potential as a multifunctional natural resource for sustainable strategies in dengue control.